Work integrated learning for engineering qualifications: a spanner in the works?. Issue 8 (16th November 2016) - Mutereko, Sybert; Wedekind, Volker
Abstract : Work - integrated learning (WIL) has been identified as a way of equipping graduates with attributes that make them work-ready. Many higher education institutions (HEIs) require their students to go through a compulsory work place learning form (WPL) of WIL. The complications of WPL can affect HEIs' student throughput. To address this challenge, a university of technology (UoT) in South Africa is curriculating engineering diplomas and degrees which do not make WPL a compulsory module. This is in line with the new Higher Education Qualifications Sub-framework and Engineering Council of South Africa requirements. We employed in-depth interviews to gain an insight into the new programmes without WPL. Our findings indicate that WPL, in its current form, does not make graduates work-ready. Employers use it either to get extra cheap labour or as a recruitment process. It is envisaged that the new programme will increase the UoT's throughput without adverse effects on the graduates' attributes. These findings have important implications for HEIs, students and employers. It implies that HEIs will greatly improve throughput, which is desirable for both the HEIs and the students. For employers, this means they will have qualified people who might need higher wages, in comparison with students on WPL and they will need to plan for more in-house induction.